Left Subclavian Artery Sacrifice in Acute Aortic Dissection Repair using the Frozen Elephant Trunk - Goebel, Nora; Holder, Simone A.; Huether, Franziska; Bail, Dorothee H. L.; Franke, Ulrich F. W. (The Thoracic and Cardiovascular Surgeon, 2022)
Objective Surgery of acute aortic dissection using the frozen elephant trunk (FET) can be complicated when the origin of the left subclavian artery (LSA) is dissected and sacrifice by ligation is a viable option. However, the LSA is supposed to play a role in neuroprotection as a major collateral. We, therefore, analyzed our results of LSA sacrifice in this cohort.Methods We identified a total of 84 patients from our prospectively collected database who underwent FET repair of acute aortic dissection between October 2009 and April 2018. LSA was sacrificed in 19 patients (22.6%). Results were analyzed and compared with regard to neurological outcomes.Results New postoperative stroke was seen in two patients (2.4%) and spinal cord injury in three patients (3.6%) overall, none in the LSA-sacrifice group. We observed a temporary neurological deficit in five patients (6.0%) overall, none in the LSA-sacrifice group. None of the patients developed acute ischemia of the left arm. Only two patients (12.5%) came back for carotid-subclavian artery bypass due to exertion-induced weakness of the left arm 3 to 4 months after the initial surgery. In-hospital mortality was 15.5% overall, with no difference between groups.Conclusion LSA sacrifice was not associated with elevated postoperative risk of either central or spinal neurological injury. Thus, it can facilitate FET repair of acute aortic dissection in selected cases when the left subclavian origin cannot be preserved. Carotid-subclavian artery bypass became necessary in only a small fraction of these patients and can be performed as a second-stage procedure.
Keywords: aorta/aortic; artery/arteries (includes all peripheral arteries); cardiac; hypothermia/circulatory arrest; outcomes (includes mortality and morbidity); spinal cord